Poly-Herbal Extract: A Promising Approach for Mitigating Gastric Ulcers in Rat Models - Mudagal, Manjunatha P; M V, Madhu; H R, Nikhil; D, Nithish Kumar; R, Uday; R, Jagadeesh (Defence Life Science Journal, 2024)
A prevalent condition that affects humans is stomach ulcers. The constraints and rapid expansion of civilization, particularly a stressful lifestyle, are contributing to an increase in the occurrence of ulcers. New synthetic pharmaceuticals and herbal drugs must fulfil global quality, safety, and efficacy criteria as Western medicine progresses. The stomach mucosa breaks down into gastric ulcers, which have a diameter greater than 5 mm and extend into the muscularis mucosa. Changes in the stomach’s defence mechanisms may alter the gastric mucosa, resulting in erosion and ultimately ulceration. This study aims to explore the potential of tamarind seed and aloe vera extracts in mitigating gastric ulcers, presenting a natural alternative to NSAID-induced ulcer treatment. The herbal extract’s effectiveness in reducing oxidative stress and gastric mucosal damage was assessed in comparison to omeprazole. The anti-ulcer activity was assessed using approximated biochemical parameters, and in a dose-dependent manner, the outcomes were statistically noteworthy in contrast to the rats in the ulcer group.